Safety on highways by customizing vehicular ad hoc networks - Venkatesan, M.; raja, Dr. S. Selvakumar (International Journal of Engineering and Technology, 2018)
In this paper, the Intelligent Transport Systems (ITS) is used for improving the road safety on highways. It is sharing information about traffic conditions to other vehicles (Vehicle to Vehicle Communications). This methodologies improvement is now available in vehicular ad hoc networks (VANET). The packet success prospect is acquired first for link of vehicles by fetching multiple users’ disturbance, rout loses. By considering the delay constraints and types of possibility crash, the optimized channel access probabilities are approximated. Finally the current methodologies customizing the channel access probabilities in Vehicular ad-hoc networks. The NS2 simulation output denote the reduction of traffic crash possibilities difference with same channel access probabilities in optimal range, thus it has vast advantages in other non-ideal systems.